2007
DOI: 10.1016/j.juro.2007.01.114
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry Products Inhibit Adherence of P-Fimbriated Escherichia Coli to Primary Cultured Bladder and Vaginal Epithelial Cells

Abstract: Purpose-Cranberry proanthocyanidins have been identified as possible inhibitors of Escherichia coli adherence to uroepithelial cells. However, little is known about the dose range of this effect. Furthermore, it has not been studied directly in the urogenital system. To address these issues we tested the effect of a cranberry powder and proanthocyanidin extract on adherence of a P-fimbriated uropathogenic E. coli isolate to 2 new urogenital model systems, namely primary cultured bladder epithelial cells and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
2
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 21 publications
(1 reference statement)
5
147
2
9
Order By: Relevance
“…27 In vitro studies have demonstrated this adherence inhibition with proanthocyanidin extract from cranberries, human urine collected after cranberry ingestion, and growth of E coli on cranberry-containing media. 9,27,28 None of these previous in vitro studies longitudinally evaluated clinical outcomes. Similarly, none of the clinical studies correlated observed patient outcomes with in vitro findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In vitro studies have demonstrated this adherence inhibition with proanthocyanidin extract from cranberries, human urine collected after cranberry ingestion, and growth of E coli on cranberry-containing media. 9,27,28 None of these previous in vitro studies longitudinally evaluated clinical outcomes. Similarly, none of the clinical studies correlated observed patient outcomes with in vitro findings.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In vitro data have shown that cranberry inhibits primarily P-fimbriated uropathogenic strains of Escherichia coli from adhering to uroepithelial cells, which is a critical step in the development of UTI. [7][8][9] However, these findings have not been correlated directly with clinical outcomes or verified in clinical studies.…”
mentioning
confidence: 97%
“…More virulent E. coli causing pyelonephritis and complicated UTI typically bear p-fimbriae in addition to type-1 fimbriae. Adhesion of p-fimbriated E. coli with their specific lectins [9][10][11] is not inhibitable by fructose or other low molecular carbohydrates (hence mannose-resistant fimbriae).…”
Section: Anti-adhesion Effects As Putative Anti-infective Mechanismmentioning
confidence: 99%
“…Taniny te zapobiegają tworzeniu się fimbrii typu P na ścianie bakterii Escherichia coli, hamując w ten sposób możli-wości adhezji drobnoustrojów do komórek urotelium. Blokowanie powstawania fimbrii bakterii odgrywa kluczową rolę w zapobieganiu kolonizacji i jest zależne od dawki proantocyjanidyn [21]. Badanie z randomizacją nad wpływem koncentratu soku żurawinowo-borówko-wego w dawce 50 ml 4 razy dziennie istotnie zmniejszało ryzyko nawrotu infekcji układu moczowego u kobiet [22].…”
Section: Czynniki Dietetyczneunclassified